2022
DOI: 10.1021/acsomega.2c02439
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Aza-Piancatelli Reaction: Scope and Limitations of Furan Substitution in Donor–Acceptor Stenhouse Adduct Synthesis

Abstract: The aza-Piancatelli reaction has been widely used to synthesize donor–acceptor Stenhouse adducts (DASAs), a new class of molecular photoswitches with unique properties. However, the substitution pattern of furan cores has been limited to position 3, as 3,4-disubstituted furans remain unreactive. Herein, we explore the aza-Piancatelli reaction mechanism using density functional theory (DFT) calculations to understand the influence of the different substituents on the reactivity. We found that all the reaction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…DASA stability and their tendency to undergo the retro-reaction as a function of different substitution patterns on the triene bridge have also been studied by DFT calculations. 73 In addition, acid triggered in situ formation of Stenhouse salts from DASAs was observed, which most likely proceeded via a retro-reaction to the furan adduct with subsequent release of furfural. 107 A mechanistic characterization of this dissociative side reaction has not yet been reported.…”
Section: Dasa-containing Polymersmentioning
confidence: 97%
See 4 more Smart Citations
“…DASA stability and their tendency to undergo the retro-reaction as a function of different substitution patterns on the triene bridge have also been studied by DFT calculations. 73 In addition, acid triggered in situ formation of Stenhouse salts from DASAs was observed, which most likely proceeded via a retro-reaction to the furan adduct with subsequent release of furfural. 107 A mechanistic characterization of this dissociative side reaction has not yet been reported.…”
Section: Dasa-containing Polymersmentioning
confidence: 97%
“…Limited DASA stability from retro-formation of the starting materials has also recently been observed or predicted in studies of various small molecule DASAs in solution. 36,73,79,107 It was reported that a DASA composed of an indoline donor and a Meldrum's acid-based acceptor with methyl substitution at position 5 of the triene bridge led to release of the amine and recovery of the furan adduct when in solution overtime. 36 This reaction was shown to be faster in more polar solvents such as methanol.…”
Section: Dasa-containing Polymersmentioning
confidence: 99%
See 3 more Smart Citations